Comparison of the Effectiveness of Interventions to Reduce Smoking in Ecuadorian Patients with Cardiovascular Diseases - Elsy Labrada González; Angélica Victoria Martínez Herrera; Manuel Conrado Ezcurdia Bárzaga (Medisur)
Foundation: cardiovascular diseases are the main cause of death worldwide. Tobacco consumption constitutes a relevant risk factor. There are numerous therapeutic proposals from different health disciplines with the aim of facilitating the transition from habitual consumption to quitting tobacco. Objective: to compare the effectiveness of interventions to reduce smoking in Ecuadorian patients with cardiovascular diseases treated at a hospital in Quito, Ecuador. Methods: a quasi-experimental study was carried out, before-after without a control group. The study population was made up of 135 patients from a hospital in Quito, Ecuador, with cardiovascular diseases. The effectiveness of three interventions was evaluated: cognitive behavioral therapy, medication therapy, and support programs. Cochran's Q test was used with SPSS software. Results: cognitive-behavioral therapy was rated as effective by 71.1 % of patients, support programs were considered ineffective in 57.8 %. A Cochran's Q statistic equal to 21.733 (p < 0.001) was obtained, which represented a significant difference between the efficacies of the interventions. Conclusions: there were substantial differences between the efficacies of the interventions to reduce smoking. Cognitive behavioral therapy was rated as the most effective.